SIKAP PENGUNJUNG TERHADAP KETERSEDIAAN LAYANAN DI READING LIGHTS (Studi Deskriptif Kuantitatif Sikap Pengunjung Terhadap Ketersediaan Layanan Reading Lights Coffee & Corner) - Nina Nopianti; Tine Silvana; Agung Budiono (Universitas Padjadjaran, 2016)
This study discusses the users attitudes of the availability of services in Reading Lights. This study was conducted to determine how the visitor attitudes towards availability of services in Reading lights. The research method used is quantitative method with a descriptive approach. Data collection methods used in this study are questionnaires, interviews, observation, and literature study. The population in this study are the visitors Reading Lights by taking a sample of 50 respondents. The results obtained show that the attitude of the visitors are comprised of aspects of knowledge (cognitive) visitors agreed to know the service availability in Reading Lights, Impression (affective) visitors agreed include aspects of respondents' feelings agreed include aspects of respondents' feelings about the provision of foreign language collection, behavior (conative) visitors tend to always want to come to Reading Lights. The conclusion of this study is Cognitive Aspects (Knowledge) visitors to the availability of services and Coffee Corner Reading Lights which includes knowledge about the services available in the Reading Lights, collections and facilities support(favorable), Aspects of Affective (feeling) of visitors to the availability of services Reading Light and Coffee Corner, which includes a sense of excitement/love to the services available in the Reading Lights, collections and facilities in general support (favorable), Aspect Conative (Behavior) of visitors to the availability of the service Light Reading and Coffee Corner, which includes the respondent wishes to come, read/buy a book, use the reading room, use the facilities and tell other people about Reading Lights that generally supports (favorable).This is evident from the questionnaire in the results research to be a reference to improve the Reading Lights service.Penelitian ini membahas sikap pengunjung terhadap ketersediaan layanan di Reading Lights. Penelitian ini dilakukan untuk menggambarkan bagaimana sikap pengunjung terhadap ketersediaan layanan di Reading Lights. Metode penelitian yang digunakan ialah metode kuantitatif melalui pendekatan deskriptif. Metode pengumpulan datan yang digunakan dalam penelitian ini adalah kuesioner, wawancara, observasi dan studi literatur. Populasi dalam penelitian ini ialah pengunjung Reading Lights, yang diambil sampel 50 responden. Hasil penelitian menunjukkan bahwa sikap pengunjung terdiri dari aspek pengetahuan pengunjung (kognitif) setuju untuk mengetahui ketersediaan layanan di Reading Lights, perasaan pengunjung (afektif) meliputi aspek perasaan responden tentang ketersediaan layanan koleksi bahasa asing, prilaku pengunjung (konatif) cenderung selalu ingin datang ke Reading Lights. Kesimpulan dari penelitian ini ialah aspek pengetahuan pengunjung (kognitif) dalam sikap ketersediaan layanan dan Coffee Corner Reading Lights meliputi pengetahuan mengenai layanan yang tersedia di Reading Lights, koleksi dan fasilitas pendukung (favorable), aspek perasaan pengunjung (afektif) mengenai ketersediaan layanan Reading Lights dan Coffee Corner meliputi perasaan senang/cinta kepada layanan yang tersedia di Reading Lights, koleksi dan fasilitas pendukung (favorable). Aspek prilaku pengunjung (konatif) mengenai ketersediaan layanan Reading Lights dan Coffee Corner, mencakup responden ingin datang, membaca/membeli buku, menggunakan ruang baca, menggunakan fasilitas dan memberitahu orang lain tentang Reading Lights yang umumnya mendukung (favorabel). Hal ini terlihat dari hasil kuesioner penelitian yang diharapakan menjadi acuan untuk meningkatkan layanan di Reading Lights.